Peningkatan Kemampuan Mengenal Bentuk Geometri Melalui Permainan Papan Monopoli Pada Anak Usia 5-6 Tahun - Uar Wartini; Dewi Siti Aisyah; Nancy Riana (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve the ability to recognize geometric shapes in children aged 5 -6 years, through Monopoly Board media. The subjects of this study were 15 children aged 5-6 years in Kindergarten Az-zahra 2 Karawang. The research method carried out by the researcher is a classroom research method, research data is collected by observation and documentation techniques using observation guidelines for the ability to recognize geometric shapes, the results of the study show that playing monopoly board has an effect on the ability to recognize geometric shapes. This is evidenced by the difference in the results of the ability to recognize geometric shapes before the research was held, the results were 37%, while after conducting research using the Monopol board game, the results became 67% in the first cycle, then in the second cycle it rose to 87%, after conducting research with the media. Monopoly board the development of recognizing geometric shapes in children has experienced significant development, then it is suggested to the Early Childhood Education Institution to implement monopoly board playing activities as an alternative to stimulate children's cognitive abilities, especially in an effort to increase children's recognition of geometric shapes.